An exploratory study into the impact of NACCQ Research - Clear, Tony; Young, A. (NACCQ, 2007)
This paper reports the findings of a preliminary investigation into the impact of research within the New Zealand National Advisory Committee on Computing Qualifications (NACCQ) sector. Using a strategy based predominantly upon keyword search of academic reference databases, the study found that NACCQ projects and publications are beginning to be cited in diverse outlets, and are now making a contribution to the international literature in the computing disciplines. The study and its findings are briefly reviewed and the outlets in which NACCQ research has been cited are tabulated. This paper establishes the first profile of international citations for NACCQ research and provides a replicable baseline for subsequent studies into the impact of research originating in the sector.